Pengaruh Pendidikan Kesehatan Tentang HIV-AIDS Melalui Buku Cerita Terhadap Tingkat Pengetahuan, Sikap, Dan Daya Terima Remaja Dalam Pencegahan HIV-AIDS Di SMA - Trianto, Agung, Yuli Kusumawati, SKM., M. Kes (Epid), Kusuma Estu Werdani, SKM., M.Kes (2015)
AIDS (Acquired Immunodeficiency Syndrome) one of diseases that has the highest number of sufferers in the world. It becomes a global problem. The purpose of this study is to analyze the effect of health education on HIV-AIDS through the book story on the level of knowledge, attitude, and power of acceptancet within adolescent HIV-AIDS prevention in Senior High School. This research uses Quasi Experimental with Pretest-Posttest Design with Control Group and Pre Eksperimental with Posttest Only Design. The population in this study were 10 and 11 grade in senior high school as many as 732 students. The sample' selection uses Simple Random Sampling, it is divided into three groups,there are the experimental group, the control group, and the group power of acceptancet with 120 samples. Statistical test using Paired sample t-test showed there is no difference in the average score of knowledge (p = 0.000) and attitude (p = 0.000) in the experimental group after treatment and there is no difference in the average score of knowledge (p = 0.000) and attitude (p = 0.000) in the control group. Independent sample t-test results there is no difference in the effect of health education on HIV-AIDS between using storybook and LCD on knowledge (p = 0.577) and attitude (p = 0.763) adolescents in the prevention of HIV-AIDS. For teens acceptance of the storybook, almost respondents particularly like the storybook as many as 25 respondents (62.5%).